Value-at-Risk and expected shortfall for rare events - Stefan Mittnik; Tina Yener (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We show that the use of correlations for modeling dependencies may lead to counterintuitive behavior of risk measures, such as Value-at-Risk (VaR) and Expected Short- fall (ES), when the risk of very rare events is assessed via Monte-Carlo techniques. The phenomenon is demonstrated for mixture models adapted from credit risk analysis as well as for common Poisson-shock models used in reliability theory. An obvious implication of this finding pertains to the analysis of operational risk. The alleged incentive suggested by the New Basel Capital Accord (Basel II), amely decreasing minimum capital requirements by allowing for less than perfect correlation, may not necessarily be attainable.
urn:nbn:de:hebis:30-56871
Keywords: C52; G11; G32; 330; Operational Risk; Latent Variables; Correlated Events; Value at Risk; Bankrisiko; Korrelation; Multivariate Analyse; Basel II; Theorie